Anger, Forgiveness, and Restorative Justice in Light of Clerical Sexual Abuse and Its Cover-up - Pope, Stephen J. (Theological studies, 2019)
Catholic tradition provides resources for understanding morally legitimate anger as ordered to the good of survivors and their wider communities, a way of conceiving of forgiveness as a caritas-inspired decision to willing what is authentically good for an offender, including just retributive measures, and support for employing practices of restorative justice as a means of addressing clerical sexual abuse and its cover-up.